Nationwide Cohort Study of Antiretroviral Therapy Timing: Treatment Dropout and Virological Failure in China, 2011–2015. (16th May 2018) - Zhao, Yan; Wu, Zunyou; McGoogan, Jennifer M; Sha, Yiyi; Zhao, Decai; Ma, Ye; Brookmeyer, Ron; Detels, Roger; Montaner, Julio S G
Abstract : Initiating antiretroviral therapy (ART) quickly after diagnosis (i.e., within 30 days) was associated with significantly reduced treatment dropout and virological failure compared to delayed treatment, providing evidence that immediate ART initiation is critical to individual and public health. Abstract: Background: People living with human immunodeficiency virus (PLWH) are still being diagnosed late, rendering the benefits of "early" antiretroviral therapy (ART) unattainable. Therefore, we aimed to evaluate the benefits of "immediate" ART. Methods: A nationwide cohort of PLWH in China who initiated ART January 1, 2011, to December 31, 2014 and had baseline CD4 results >200 cells/μL were censored at 12 months, dropout, or death, whichever came first. Treatment dropout and virological failure (viral load ≥400 copies/mL) were measured. Determinants were assessed by Cox and log-binomial regression. Results: The cohort included 123605 PLWH. The ≤30 days group had a significantly lower treatment dropout rate of 6.72%, compared to 8.91% for the 91–365 days group and to 12.64% for the >365 days group. The ≤30 days group also had a significantly lower virological failure rate of 5.45% (31–90 days: 7.39%; 91–365 days: 9.64%; >365 days: 12.67%). Greater risk of dropout (91–365 days: adjusted hazard ratio [aHR] = 1.33, 95% confidence interval [CI] = 1.25–1.42; >365 days: aHR = 1.55, CI = 1.47–1.54), and virological failure (31–90 days: adjusted risk ratio [aRR] = 1.35, CI = 1.26–1.45; 91–365 days: aRR = 1.66, CI = 1.55–1.78; >365 days: aRR = 1.85, CI = 1.74–1.97) were observed for those who delayed treatment. Conclusions: ART within 30 days of HIV diagnosis was associated with significantly reduced risk of treatment failure, highlighting the need to implement test-and-immediately-treat policies.